Sebuah Smart Rumpon Portable berbasis Solar Cell dan LoRa untuk Meningkatkan Produktivitas Nelayan Tradisional Pantai Puger Kulon - Haryati, Jihan Rahfida; Muhammad Rifki Afdillah; Tio Alfian Nirvanto; Dimas Kharisma Rezkie Pamungkas; Anfasa Syahrul Habibie; Risse Entikaria Rachmanita (Universitas Muhammadiyah Metro, 2024)
Puger Kulon Coast Fishermen are traditional fishermen who still rely on decreasing knowledge and simple catch tools in searching for fish. Fishers experience a variety of challenges in finding fish due to various factors such as, seasons, climate, uncertain weather, and the limitation of catch devices making them difficult to find fish. This activity aims to provide a solution to the problems experienced by our partners, the traditional fishermen in the village of Puger Kulon. The problem that the partners are experiencing is the instability of the catch. The methods of implementation of these activities include the study of literature, socialization, preparation of tools and materials, planning and design of tools, implementation and testing tools, supporting and training in the use of instruments, and evaluation. The Electronic Calling Tool can be used for up to 13 hours on full battery, but it is recommended that partners use the device for a maximum of 8 hours to extend the device's service life. Implementation of the program has gone well and achieved good results demonstrated by increased catch yields of 28% and fuel savings of 20%. The system and components of the eFAD must be regularly monitored and controlled according to the program implementation guidelines given.